FAMILY CONTROL DALAM MEMODERASI PENGARUH BOARD GENDER DIVERSITY, RISK MANAGEMENT COMMITTEE DAN DUALITAS CEO TERHADAP NILAI PERUSAHAAN - Laela Nurul Safa'ah; Abdul Aziz Nugraha Pratama (JURNAL AKUNTANSI, 2023)
This research aims to find out how board gender diversity, risk management committee and CEO duality affect corporate value moderated by family control. This type of research is quantitative research using panel data sourced from secondary data through an annual report that has been published on the website www.idx.co.id. By using a purposive sampling technique, 15 manufacturing companies were found that met the criteria to be used as research samples. After testing using the SPSS 26 tool, it can be seen that the board variable gender diversity has a positive and significant effect on firm value, risk management committee and family control has a negative and significant effect on firm value, and CEO duality has negative and insignificant results. Furthermore, family control is able to moderate board gender diversity and risk management committee variables in influencing firm value. Meanwhile, CEO duality cannot be moderated by family control.